Dynamics of Islamic Education Management and Its Impact on Academic Service Effectiveness in Islamic Higher Education - Indrawan, Irjus; Refika, Refika (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the dynamics of Islamic educational management and its impact on academic services at Islamic higher education institutions. Using a descriptive qualitative approach, the study utilised interviews, participant observation, and documentation to understand the impact of Islamic managerial values on the quality of academic services. The results indicate a strong link between management elements—planning, organising, Islamic leadership, supervision (hisbah), and continuous evaluation—and service effectiveness, as reflected in a structured system, student satisfaction, and the quality of academic processes. The integration of Islamic values , such as amanah (trust), musyawarah (deliberation), ihsan (excellence), and justice, creates a service culture grounded in spirituality and oriented toward humanity. The study confirms that these values strengthen planning, organisation, leadership, supervision, and evaluation, which in turn enhance the service structure, process quality, and student satisfaction. This study offers a conceptual and practical framework for Islamic higher education institutions to enhance the quality of academic services, and encourages further research utilising quantitative and cross-institutional approaches.